2017
DOI: 10.3168/jds.2016-11671
|View full text |Cite
|
Sign up to set email alerts
|

A combination of lactic acid bacteria regulates Escherichia coli infection and inflammation of the bovine endometrium

Abstract: Uterine function in cattle is compromised by bacterial contamination and inflammation after calving. The objective of this study was to select a combination of lactic acid bacteria (LAB) to decrease endometrium inflammation and Escherichia coli infection. Primary endometrial epithelial cells were cultured in vitro to select the most favorable LAB combination modulating basal tissue inflammation and E. coli infection. Supernatants were obtained to determine expression of pro-inflammatory cytokines, and E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 45 publications
3
36
0
2
Order By: Relevance
“…The immunostimulatory effects for lactobacilli were also observed in earlier studies 19 , 56 , 57 and the present study also suggests that lactobacilli are supportive for the containment of these pathogenic bacteria. It was also shown that a distinct lactobacilli strain alone or in combination with other reduced an E. coli infection and affected the pro-inflammatory reaction in bovine endometrial cells in vitro 58 , 59 .…”
Section: Discussionmentioning
confidence: 97%
“…The immunostimulatory effects for lactobacilli were also observed in earlier studies 19 , 56 , 57 and the present study also suggests that lactobacilli are supportive for the containment of these pathogenic bacteria. It was also shown that a distinct lactobacilli strain alone or in combination with other reduced an E. coli infection and affected the pro-inflammatory reaction in bovine endometrial cells in vitro 58 , 59 .…”
Section: Discussionmentioning
confidence: 97%
“…Similar to fecal microbiota transplantation, vaginal microbiota transplantation is used to restore the mucosal microbiota imbalance by re-establishing beneficial vaginal microbial communities [15]. In dairy cows, it has been observed that the use of lactic acid bacteria (LAB) confers a health benefit to the reproductive tract against bacterial infections [16][17][18][19]. Little is known about the presence of LAB in ovine vaginal tract [20] and there is a lack of research regarding the utilization of probiotics during synchronization protocols to improve reproductive performance.…”
Section: Introductionmentioning
confidence: 99%
“…kwas mlekowy, kwas octowy, etanol oraz reuterycyklinę. Wykazano, iż L. reuteri stanowi obiecującą broń w przeciwdziałaniu infekcjom wywołanym przez H. pylori, E.coli, C. difficile oraz bakterie z rodzaju Salmonella [39][40][41][42]. H. pylori jest patogenem związanym bezpośrednio z rozwojem nowotworu żołądka, E. coli związana jest pośrednio z rozwojem nowotworu jelita grubego [43], nowotworem przełyku [44] i wątroby [45].…”
Section: Bakterie Jogurtowe a Komensalna Mikroflora Jelitunclassified